Player session rating of perceived exertion: A more valid tool than coaches` ratings to monitor internal training load in elite youth female basketball - Lupo, C.; Ungureanu, A. N.; Frati, R.; Panichi, M.; Grillo, S.; Brustio, P. R. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To monitor elite youth female basketball training to verify whether players` and coaches` (3 technical coaches and 1 physical trainer) session rating of perceived exertion (s-RPE) has a relationship with Edwards` method. Methods: Heart rate of 15 elite youth female basketball players (age 16.7 [0.5] y, height 178 [9] cm, body mass 72 [9] kg, body mass index 22.9 [2.2] kg·m-2) was monitored during 19 team (268 individual) training sessions (102 [15] min). Mixed effect models were applied to evaluate whether s-RPE values were significantly (P=.05) related to Edwards` data, total session duration, maximal intensity (session duration at 90-100% HRmax), type of training (ie, strength, conditioning, and technique), and whether differences emerged between players` and coaches` s-RPE values. Results: The results showed that there is a relationship between s-RPE and Edwards` methods for the players` RPE scores (P=.019) but not for those of the trainers. In addition, as expected, both players` (P=.014) and coaches` (P=.002) s-RPE scores were influenced by total session duration but not by maximal intensity and type of training. In addition, players` and coaches` s-RPE values differed (P<.001)—post hoc differences emerged for conditioning (P=.01) and technique (P<.001) sessions. Conclusions: Elite youth female basketball players are better able to quantify the internal training load of their sessions than their coaches, strengthening the validity of s-RPE as a tool to monitor training in team sports.